Integrasi Integrasi Game Based Learning dalam Pendidikan Agama Katolik: Integrasi Game Based Learning dalam Pendidikan Agama Katolik - Sergius Lay; Natalia Harefa; Selvianti Dakhi; Anisa Putri Hulu; Ester Fosumange Laia (STP St. Bonaventura Medan, 2026)
The development of digital technology demands pedagogical innovation in Catholic Religious Education (CRE), particularly at the Catholic Junior High School (SMPK) level. One emerging approach is Game-Based Learning (GBL). This study aims to systematically analyze the integration of GBL in CRE and to formulate its pedagogical implications for improving the quality of learning. The research employs a Systematic Literature Review method, with data sources drawn from Google Scholar, ERIC, Scopus, and Garuda within the 2019–2025 period. The initial search yielded 132 articles, and after a selection process based on inclusion and exclusion criteria, 28 articles were analyzed in depth. The synthesis results indicate that GBL is effective in enhancing students’ motivation and engagement; however, most studies still focus on cognitive aspects and have not extensively explored the dimension of faith formation. Therefore, the integration of GBL in CRE needs to be situated within a holistic faith pedagogy framework through stages of strengthening faith content, contextual game design, active engagement, value reflection, and the internalization and transformation of attitudes. This study contributes conceptually by proposing an integrative framework of GBL in CRE and offers practical implications for junior high school teachers in designing innovative and reflective learning.